The Health and Welfare Effects of Increases in Workers’ Compensation Benefits - Jinks, Lu (Journal of Labor Economics, 2023)
This paper estimates the causal impacts of workers’ compensation income benefits on workers’ health and welfare outcomes. Using claims data from 2004 to 2016, I explore the variation in benefits due to a reform of New York workers’ compensation that increased the maximum weekly benefits. I find that a $77 increase in the weekly benefits led to an additional 3.4 days off work. Medical utilization did not increase. Each extra day off work decreased the reinjury likelihood by 2.9%. The current benefit level in New York is close to optimal in balancing payer cost and worker health outcomes.